How the Management of Children With Congenital Central Hypoventilation Syndrome Has Changed Over Time: Two Decades of Experience From an Italian Center - Porcaro, Federica; Paglietti, Maria Giovanna; Cherchi, Claudio; Schiavino, Alessandra; Chiarini Testa, Maria Beatrice; Cutrera, Renato (Frontiers in Pediatrics, 2021)
Background: Congenital Central Hypoventilation Syndrome (CCHS) is a rare disorder whose clinical phenotype is closely related to genotype. Methods: a retrospective analysis has been conducted on 22 patients with CCHS referred to Pediatric Pulmonology and Respiratory Intermediate Care Unit of Bambino Gesù Children’s Hospital (Italy) for a multidisciplinary follow-up program between 2000 and 2020. Results: apnea and cyanosis were the most frequent symptoms at onset (91%). Overall, 59% of patients required tracheostomy and invasive mechanical ventilation (IMV) in the first months of life. 32% of patients had Hirschsprung disease that was associated with longer polyalanine repetitions or non-polyalanine expansion mutations (NPAMs). Polyalanine expansion mutations (PARMs) were more frequent and two novel NPARMs (c.780dupT, C.225_256delCT) were described in 14% of patients. Focal epilepsy was firstly described in 14% of patients and neurocognitive and neuromotor impairment involved 27% and 23% of children, respectively. Symptoms due to the Autonomic Nervous System (ANS) dysfunction – including strabismus (27%), dysphagia (27%), abnormal heart rhythm (10%), breath holding spells (9%) and recurrent seizures due to hypoglycemia (9%) – were associated with an increased number of polyalanine repetitions of exon 3 or non-polyalanine repetition mutations of PHOX2B gene. Overall, the number of patients with moderate-severe phenotype initially treated with non-invasive ventilation (NIV) increased over time, and three patients started IMV concluded the decannulation program. Conclusions: our study confirms that more severe phenotypes of CCHS are related to the number of polyalanine repetitions or to non-polyalanine expansion mutations. Although invasive ventilation is often required by patients with severe genotype/phenotype, gradual acquisition of specific skills in the management of patients with CCHS and technological improvements in mechanical ventilation allowed us to improve our therapeutic approach in this population.